2010
DOI: 10.1136/bjsm.2010.079822
|View full text |Cite
|
Sign up to set email alerts
|

IOC consensus paper on the use of platelet-rich plasma in sports medicine

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde ubetydelige forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på bjsm.bmj.com: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
186
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(199 citation statements)
references
References 89 publications
4
186
1
8
Order By: Relevance
“…The 2010 International Olympic Committee consensus paper on the use of PRP in sports medicine concluded that PRP is a treatment option for chronic tendon injuries [14]. However, further study is required to identify the optimal PRP preparation, dosing protocol, and timing for various tendon disorders.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2010 International Olympic Committee consensus paper on the use of PRP in sports medicine concluded that PRP is a treatment option for chronic tendon injuries [14]. However, further study is required to identify the optimal PRP preparation, dosing protocol, and timing for various tendon disorders.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…This was a retrospective study with no untreated control patients. However, the 2010 International Olympic Committee consensus paper on the use of PRP in sports medicine concluded that there was little scientific support for the use of PRP in muscle strain injuries [14].…”
Section: Applicability Of Prp Therapies To Muscle Injuriesmentioning
confidence: 99%
“…The evidence base to guide the use of PRP in the treatment of contusion injuries and muscle strains is very limited. An International Olympic Committee (IOC) consensus paper on the use of PRP in sports medicine indicated there is little scientific support for PRP in the treatment of muscle strain injury and suggested further investigation utilizing this technology is needed to develop practice guidelines [2].…”
Section: Introductionmentioning
confidence: 99%
“…The alpha granules are the most studied platelet structures (each platelet has 50-80 alpha units, and each granule has more than 30 bioactive proteins that can be released by a stimulus). There are different subpopulations of alpha granules, and an early release of these granules by activation with thrombin may promote an exacerbated reaction, leading to the antagonistic action of growth factors, and these factors should be released at different stages of the healing process 15 . In addition, the previous activation can limit the percutaneous application, which is the preferred route used in conservative treatment, owing to the gelation PRP after activation.…”
mentioning
confidence: 99%